Tumour Heterogeneity and Disease Infiltration as Paradigms of Glioblastoma Treatment Resistance - Pulkit Malhotra; Ruman Rahman (Onco)
Isocitrate dehydrogenase wild-type glioblastoma, a Grade 4 malignant brain neoplasm, remains resistant to multimodal treatment, with a median survival of 16 months from diagnosis with no geographical bias. Despite increasing appreciation of intra-tumour genotypic variation and stem cell plasticity, such knowledge has yet to translate to efficacious molecular targeted therapies in this post-genomic era. Critically, the manifestation of molecular heterogeneity and stem cell biological process within clinically relevant infiltrative disease is little understood. Here, we review the interactions between neural plasticity, intra-tumour heterogeneity and residual infiltrative disease, and we draw upon antibiotic resistance as an insightful analogy to further explain tumour heterogeneity.